2006
DOI: 10.1007/s10787-006-1499-3
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive and anti-inflammatory effects of the ethyl acetate stem bark extract of Bridelia scleroneura (Euphorbiaceae)

Abstract: Bridelia scleroneura is a member of the Euphorbiaceae family. In folk medicine in Cameroon, the stem bark of this plant is used for relieving abdominal pain, contortion, arthritis and inflammation. In this study, the antinociceptive and anti-inflammatory activities of the ethyl acetate stem bark extract have been evaluated. The putative analgesic effect of the plant extract was examined in abdominal constriction, hot plate, formalin and on pain using tail immersion mouse models and in carrageenan-induced paw e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 23 publications
3
8
0
Order By: Relevance
“…Lupeol, a pentacyclic lupane-type triterpene contains significant biological properties such as antiprotozoal activity [27,28], anticancer [29], antimicrobial activity [30] and anti-inflammation [31]. This triterpene is found in various types of plants such as Bridelia scleroneura [32], Millettia versicolor [33] and Euclea natalensis [27]. Our study showed that C. hystrix leaves are a lupeol source, concurring with the findings of Anuchapreeda et al [34].…”
Section: Discussionsupporting
confidence: 91%
“…Lupeol, a pentacyclic lupane-type triterpene contains significant biological properties such as antiprotozoal activity [27,28], anticancer [29], antimicrobial activity [30] and anti-inflammation [31]. This triterpene is found in various types of plants such as Bridelia scleroneura [32], Millettia versicolor [33] and Euclea natalensis [27]. Our study showed that C. hystrix leaves are a lupeol source, concurring with the findings of Anuchapreeda et al [34].…”
Section: Discussionsupporting
confidence: 91%
“…We observed decreased TNFα and IL-8 expression after NVH treatment. Our findings indicate an NVH anti-inflammatory potential in line with anti-inflammatory properties reported in other Euphorbiaceae plant family members [ 25 ]. This anti-inflammatory effect appears to be significant only at 10 μg/mL suggesting an optimal efficient dose of NVH between 1 and 10 μg/mL.…”
Section: Discussionsupporting
confidence: 84%
“…Further the anti-inflammatory activity could also be associated with antioxidant activity of C. indica (Venkateshwaran and pari 2003a, b) since inflammatory activity of carrageenan has been demonstrated to be accompanied by elevation in the free radicals level (Gamache et al 1986). The triterpenes, lupeol and b-sitosterol have been reported to exert anti-inflammatory activities (Theophile et al 2006). Therefore, this effect may also be attributed to these constituents reported to be present in leaves of C. indica (Rastogi and Mehrotra 1998;Ray and Kundu 1987).…”
Section: Discussionmentioning
confidence: 99%